The early systemic and gastrointestinal oxygenation effects of hemorrhagic shock resuscitation with hypertonic saline and hypertonic saline 6% dextran-70: A comparative study in dogs - Braz, José Reinaldo Cerqueira [UNESP]; do Nascimento, P.; Filho, O. P.; Braz, Leandro Gobbo [UNESP]; Vane, Luiz Antonio [UNESP]; Vianna, PTG; Rodrigues, G. R. (Lippincott Williams & Wilkins, 2004)
The smaller volemic state from hypertonic (7.5%) saline (HS) solution administration in hemorrhagic shock can determine lesser systemic oxygen delivery and tissue oxygenation than conventional plasma expanders. In a model of hemorrhagic shock in dogs, we studied the systemic and gastrointestinal oxygenation effects of HS and hyperoncotic (6%) dextran-70 in combination with HS (HSD) solutions in comparison with lactated Ringer's (LR) and (6%) hydroxyethyl starch (HES) solutions. Forty-eight mongrel dogs were anesthetized, mechanically ventilated, and subjected to splenectomy. A gastric air tonometer was placed. in the stomach for intramucosal gastric CO2 (Pgco(2)) determination and for the calculation of intramucosal. pH (pHi):[pHi = pHa - log(Pgco(2)/Paco(2))].The dogs were hemorrhaged (42% of blood volume) to hold mean arterial blood pressure at 40-50 mm Hg over 30 min and were then resuscitated with LR (n = 12) in a 3:1 relation to removed blood volume; HS (n = 12), 6 mL / kg; HSD (n = 12), 6 mL / kg; and HES (mean molecular weight, 200 kDa; degree of substitution, 0.5) (n = 12) in a 1:1 relation to the removed blood volume. Hemodynamic, systemic, and gastric oxygenation variables were measured at baseline, after 30 min of hemorrhage, and 5, 60, and 120 min after intravascular fluid resuscitation. After fluid resuscitation, HS showed significantly lower arterial pH and mixed venous Po-2 and higher systemic oxygen uptake index and systemic oxygenation extraction than LR and HES (P < 0.05), whereas HSD showed significantly lower arterial pH than LR and HES (P < 0.05). Only HS and HSD did not return arterial pH and pHi to control levels (P < 0.05). In conclusion, all solutions improved systemic and gastrointestinal oxygenation after hemorrhagic shock in dogs. However, the HS solution showed the worst response in comparison to LR and HES solutions in relation to systemic oxygenation, whereas HSD showed intermediate values. HS and HSD solutions did not return regional oxygenation to control values.